2021
DOI: 10.3390/v13122537
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of SARS-CoV-2 Spike Glycoprotein 1 on Human Bronchial and Alveolar Lung Mucosa Models: Implications for Pathogenicity

Abstract: Background: The SARS-CoV-2 spike protein mediates attachment of the virus to the host cell receptor and fusion between the virus and the cell membrane. The S1 subunit of the spike glycoprotein (S1 protein) contains the angiotensin converting enzyme 2 (ACE2) receptor binding domain. The SARS-CoV-2 variants of concern contain mutations in the S1 subunit. The spike protein is the primary target of neutralizing antibodies generated following infection, and constitutes the viral component of mRNA-based COVID-19 vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Our results demonstrated that SPA4 peptide treatment significantly improved the LPS‐disrupted TEER and lung alveolar epithelial barrier function in a dose‐ and time‐dependent manner (100 μM SPA4 peptide; p < 0.05 and p = 0.0753 at 24 and 48 h, respectively, Figure 2 ). Since the H441 cells express an increased level of TLR4 even at basal level [Supplemental Figure in (Jeon et al, 2016 ), and (Rahman et al, 2021 )], it is likely that an increased treatment dose (100 μM) was needed for restoration of the epithelial barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that SPA4 peptide treatment significantly improved the LPS‐disrupted TEER and lung alveolar epithelial barrier function in a dose‐ and time‐dependent manner (100 μM SPA4 peptide; p < 0.05 and p = 0.0753 at 24 and 48 h, respectively, Figure 2 ). Since the H441 cells express an increased level of TLR4 even at basal level [Supplemental Figure in (Jeon et al, 2016 ), and (Rahman et al, 2021 )], it is likely that an increased treatment dose (100 μM) was needed for restoration of the epithelial barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed protocol and details of cellular differentiation (Club cells, goblet cells, basal cells, ciliated cells, etc.) of the bro-ALI model has been described previously and the model has been in several studies 34 , 35 , 37 41 .…”
Section: Methodsmentioning
confidence: 99%
“…The alv-ALI model was developed using NCI-H441 (ATCC HTB-174; derived from the pericardial fluid of a patient with papillary adenocarcinoma of the lung) cell line and the detailed protocol and model characteristics have been described recently 35 , 37 . The NCI-H441 cells, representative of human type II pneumocytes, express constitutively the mRNA and protein of the major surfactant apo-protein.…”
Section: Methodsmentioning
confidence: 99%
“…Reportedly, S protein (apart from the LNP-mRNA platform discussed earlier) mediates proinflammatory and/or injury (of different etiology) responses in various human cell types [102][103][104], and ACE2-mediated infection of human bronchial epithelial cells with S protein pseudovirions induced inflammation and apoptosis [105]. Also, S protein promoted an inflammatory cytokine IL-6/IL-6Rinduced trans signaling response and alarmin secretion in human endothelial cells, along with increased oxidative stress, induction of inflammatory paracrine senescence, and higher levels of leucocyte adhesion [106].…”
Section: S Protein-induced Proinflammatory Responses and Unique Gene ...mentioning
confidence: 99%